Kasih Kristus Mengilhami Sikap Sosialisme Masa Kini - Manuahe, Yani Mick R.; Manua, Englin R.; Selanno, Semuel; Thomas, Art Semuel; Dendeng, Leonardo C. (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
This article explores how the love of Christ, as taught in the New Testament, inspired socialist attitudes and its relevance in the contemporary social and economic context. Although the term socialism is not explicitly mentioned in the Bible, the essence of socialist values ​​such as togetherness, social justice, and equal distribution of prosperity is found in the teachings of Jesus Christ. The research method used is descriptive qualitative with a constructive theological approach. This article analyzes key New Testament texts to identify the practical implementation of these teachings in modern society. Christ's universal and inclusive love, as reflected in various Bible passages, teaches togetherness, sharing, special attention to the poor and oppressed, and opposition to economic injustice. By internalizing and applying the teachings of Christ's love, Christian communities can function as significant agents of change in efforts to create a more just and prosperous society.